Human herpesvirus 6 in hematologic diseases in China - XT Ma; YH Song; DM Lu; GF Mu; G Li; LX Ji; RC Yang; KF Wu (Haematologica, 2000)
BACKGROUND AND OBJECTIVE: The prevalence and pathogenic role of human herpesvirus 6 (HHV-6) in various benign and malignant hematologic diseases remain largely unknown. The aim of this study was to search for a possible involvement of HHV-6 in the pathogenesis of hematologic diseases. DESIGN AND METHODS: The presence of HHV-6 DNA sequences was examined by polymerase chain reaction (PCR) in bone marrow mononuclear cells from 241 patients with benign and malignant hematologic diseases in China. Platelet-associated immunoglobulin (PAIg) of 66 idiopathic thrombocytopenic purpura (ITP) patients was measured by competitive enzyme-linked immunosorbent assay. The presence of HHV-6 DNA in sera from 31 ITP patients was examined by PCR. Paired serum samples from 19 ITP patients were analyzed for anti-HHV-6 IgG titers using an indirect immunofluorescence assay. RESULTS: HHV-6 DNA was detected in 41% and 37.5% of ITP and acute leukemia patients respectively, but in only 6.7% of patients with iron deficiency anemia. HHV-6 positivity for ITP patients with excessive PAIgG was significantly higher than in patients with a normal level of PAIgG. HHV-6 DNA was not detected in any of the serum samples from ITP patients. None of the 19 cases of ITP showed a significant increase in anti-HHV-6 antibody titers during the convalescent phase compared with the onset phase. INTERPRETATION AND CONCLUSIONS: Our results indicate that HHV-6 infection might be associated with excessive PAIgG in some cases of ITP, and that the virus persists in a latent state. The pathogenic role of HHV-6 in ITP needs to be confirmed by further investigations.